2021
DOI: 10.1002/nag.3189
|View full text |Cite
|
Sign up to set email alerts
|

A homogenization‐based state‐dependent model for gap‐graded granular materials with fine‐dominated structure

Abstract: Gap‐graded granular soils are common natural soils composed of cohesionless granular matrix and rock aggregates. Since they are widely used as construction materials worldwide, their deformation behavior is crucial for the design of civil infrastructures. There have been rare constitutive models reported for gap‐graded granular soils in the literature. This study presents a homogenization‐based state‐dependent model within the elastoplastic framework. The model features a homogenization equation with a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Effect of Sand Fraction. The coarse aggregates (e.g., sand and gravel) usually disperse in soft clay matrix of dredged sandy clays with a fine-dominated structure, leading to a decrease of void space and compressibility [4,19,[32][33][34].…”
Section: Intrinsic Compression Curve Of Dredgedmentioning
confidence: 99%
“…Effect of Sand Fraction. The coarse aggregates (e.g., sand and gravel) usually disperse in soft clay matrix of dredged sandy clays with a fine-dominated structure, leading to a decrease of void space and compressibility [4,19,[32][33][34].…”
Section: Intrinsic Compression Curve Of Dredgedmentioning
confidence: 99%
“…It can be found from Equation ( 34 ) that also has two chances to reach zero: one is at the phase transformation state with a typical value of the fractional, the other is at the critical state with and . However, unlike the FP-n based on past stress history and other classic state-dependent models [ 8 , 53 , 54 ], Equation ( 34 ) does not require an additional empirical state parameter, e.g., , to capture the state dependence stress-dilatancy of soil, which is the main advantage of the FP-sn approach.…”
Section: Progress In Fpmentioning
confidence: 99%
“…It was found that the constitutive responses of geomaterials were state-dependent and non-associated, due to the frictional nature [ 3 , 4 , 5 , 6 ]. The associated plasticity developed for metals could not be simply employed for modelling the stress and strain behaviour of geomaterials [ 7 , 8 ]. Instead, the non-associated plasticity within the framework of critical state soil mechanics was often suggested [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contacts between particles give rise to forces with or without the consideration of friction or cohesion, and the statistical characterization of forces and contact network finally result in the stress of the overall assembly. Microscopic features, such as particle size [30,31,32], particle shape [33,34,35] and particle breakage [36,37,38,39], are also recognized to influence the macroscopic mechanical responses. For frictional granular materials, each contact is commonly assumed as elastoplastic, and the sliding is limited by the micro Coulomb friction at the contact scale.…”
Section: Introductionmentioning
confidence: 99%